Assistive Technologies (AT) Preferences of People Living with Visual Disability as Information Access Tools in Academic Libraries - Alabi, Adefunke Olanike; Okiki, Olatokunbo Christopher (International Journal of Knowledge Content Development & Technology, 2023)
Assistive technologies are necessary for ensuring independent living and equal participation in an information-based society for people living with disabilities (PLWD). This study investigated the assistive technology preference of students with visual disabilities, and the approach academic libraries should adopt in procuring assistive technologies. The study adopted a quantitative research method, with a survey as the research design. The study was conducted among visually disabled students in four public universities in Nigeria. Using the total enumeration method, an online questionnaire was used to obtain information from 151 students who voluntarily agreed to partake in the survey. The study found that access to electronic resources, scanning/conversion of print resources to electronic formats and access to information on the Web were among the technology-based services provided to visually disabled students. COBRA, ZoomText, Supernova and Dragon Naturally Speaking are the most preferred assistive technologies (software). At the same time, handheld scanners (x̅ =4.40) and braille keyboards (x̅ =4.60) are the most preferred assistive technologies in the hardware category by visually challenged students. The study further revealed that the library management should consult with students living with a visual disability before procuring assistive technology. Findings from this study thus provide further evidence of the need for librarians to fulfil their moral and legal obligation in advocating the provision of assistive technologies. Library administrators and university stakeholders should expedite actions on meeting the assistive technology needs of people living with visual disabilities. These actions should transcend mere policy formulation on the provision of assistive technologies to restructuring their services and spaces to accommodate assistive technologies as information service delivery tools for people with visual disabilities.